Modeling of mechanical properties and damage of the beam bars - Матченко, Т.І.; Радецька, Я.В. (Proceedings of National Aviation University, 2006)
The algorithm of material damage determination, based on continual and discreet material model is considered. Given ratios allow to model the mechanical properties and damages of construction material, using a beam of rods as a model. Each of rods has its own mechanical properties and prestress.